“It’s Not About Me No More”: Fatherhood and Mechanisms of Desistance Among At-Risk Men - Boonstoppel, Sarah (Journal of developmental and life-course criminology, 2019)
Purpose: Work and marriage seem out of reach for many at-risk young men, but fatherhood is relatively common. The growing body of quantitative research on parenthood and desistance from crime is mixed, yet the changes associated with the transition to fatherhood align with the mechanisms implied by theories of desistance. To understand whether and how fatherhood relates to desistance and persistence in crime, I examine how fatherhood shapes cognitive shifts and routine activities among persisting and desisting men in early adulthood. Methods: I analyze in-depth interviews with a subsample of 17 desisting and persisting fathers from the qualitative component of the Pathways to Desistance Study. Results: The meanings and structures of fatherhood experiences were sensitive to local life circumstances, yet distinct patterns emerged. Desisting fathers experienced changes in thinking, including a sense of maturity and an increase in consideration for others. Shifts often emerged from parenting experiences after the birth of a child. Desisting fathers also described time with children in terms of structured childcare activities. Persisting fathers viewed themselves as failing to fulfill role obligations and as ignoring parenthood hook for change. Persisting fathers described time with children as “babysitting” and as oriented around leisure activities. Conclusions: These findings provide insight into the lived experience of fatherhood among at-risk men. It highlights the intersection of situational and cognitive mechanisms implicated in the desistance process and supports contemporary theories of desistance and persistence.